THE ROLE OF ANALYSIS IN THE DEVELOPMENT OF FOREIGN EXCHANGE OPERATIONS OF COMMERCIAL BANKS (World Economics and Finance Bulletin, 2025)
The article will talk about the essence and classification of foreign exchange operations of commercial banks of Uzbekistan, issues of analysis of foreign exchange operations, directions of development of foreign exchange operations, analysis of the volume and share dynamics of assets, loans and deposits in foreign currency.
Keywords: currency; exchange rate currency; risk currency